Transcranial Sonography in the Diagnosis of Pituitary Tumor—A Direct Comparison With MRI - He, Lei; Zhang, Jinghan; Yu, Tengfei; Du, Yue; Liu, Xinyao; He, Wen (Frontiers in Endocrinology, 2021)
Background Transcranial sonography (TCS) is a convenient tool for detecting certain brain diseases, such as brain tumors. Few studies have reported on the use of TCS in the area of Sella turcica. The accuracy and repeatability of Sella turcica with or without pituitary tumor is not clear. Purpose This study aimed to investigate the feasibility and accuracy of TCS to measure the size of Sella turcica according to the measurement in MRI and determine its diagnostic performance in individuals with pituitary tumor. Materials and Methods In this cross-sectional comparative study, healthy volunteers and patients with pituitary tumor were enrolled for examination of TCS and MRI between October 2020 and July 2021. The transverse diameter (D1, cm) of Sella turcica and the volume of the pituitary tumor were measured by TCS and MRI, respectively, and compared by using Student’s t-test or Mann–Whitney test, using the receiver operating characteristic (ROC) curve to analyze the diagnostic value of D1 in TCS for pituitary tumor. Results A total of 75 healthy volunteers and 51 patients with pituitary tumor were evaluated. In healthy volunteers, the mean D1 was 1.30 ± 0.35 (range, 0.82–3.22) by TCS and 1.32 ± 0.29 (range, 0.94–3.02) by MRI (P = 0.054). In patients with pituitary tumor, the mean D1 was 2.0 ± 0.65 (range, 0.90–3.48) by TCS and 2.42 ± 1.0 (range, 0.80–4.70) by MRI (P = 0.000). The median measurement volume was 4.41 and 6.59 cm3 in TCS and MR, respectively (P = 0.000). The mean D1 was 1.31 ± 0.35 in healthy volunteers and 2.0 ± 0.65 cm in patients with pituitary tumor (P = 0.000). In the ROC curve analysis, the area under the curve was 0.836, and the optimal cutoff value (1.56) exhibited a sensitivity and specificity of 67.31 and 88.0%, respectively. Conclusion The consistency between the two imaging technologies performed well in D1 measurement, while the volume of the pituitary tumor was smaller as assessed by TCS than by MRI. D1 in TCS had good diagnostic performance in pituitary tumor.